Dietary supplementation of guanidinoacetic acid for sows and their progenies: Performance, blood parameters and economic viability at nursery phase - Mendonca I.B. (2019)
© 2019 Elsevier B.V.The aim of this study was to evaluate the effects of guanidinoacetic acid supplementation for sows and their litter on performance, blood parameters and economic viability of piglets at nursery phase. A total of 80 high-prolific mixed-parity sows from 3rd and 4th parity were randomly distributed between two treatments: control diet and diet supplemented with 0.1% guanidinoacetic acid. Sows were fed with the dietary treatments during the gestation and lactation. Piglets were weaned at 23 days of age and then distributed in a randomized block design, in a 2 × 2 factorial arrangement, considering two diets for the sows during gestation and lactation (control diet and diet supplemented with 0.1% GAA) and two diets for the piglets at nursery phase (control diet and diet supplemented with 0.1% GAA). Each treatment consisted of six replicates, being the pen with 40 animals considered as experimental unit. No interaction between guanidinoacetic acid supplementation for sows during the gestation and lactation and for their progenies was observed (P>0.05) on performance and blood levels of creatinine and creatine kinase of the piglets during the nursery phase. The isolated factors also did not influence (P>0.05) these parameters. There was no interaction between guanidinoacetic acid supply for sows and their progenies on economic evaluation. Piglets that received dietary supplementation of 0.1% guanidinoacetic acid presented higher average feed cost per kilogram of body weight and cost index, and also lower economic efficiency index. Dietary supplementation of 0.1% guanidinoacetic acid for sows and their litters does not influence performance and blood parameters of piglets during the nursery phase, and is economically unfeasible.